Factors Influencing the Use of Mobile Payments Among Millennials in Indonesia - Hubeis, M. Alimardi (Universitas Syiah Kuala, 2024)
Amidst the ongoing COVID-19 pandemic, mobile payment options have become vital in shaping consumer behavior, particularly among digitally savvy Indonesian millennials. Furthermore, these payment options provide a means for individuals who wish to limit their social interactions while purchasing, thereby reducing the potential for COVID-19 exposure. The author's objective in this research is to examine the diverse aspects that impact society's adoption of mobile-based payment methods. The research methodology employed in this study is qualitative, utilizing a library research technique drawing from many contemporary journals that address similar subjects. The authors identify several influential factors or variables that affect the adoption of mobile payment methods in society. These include perceived usefulness, ease of use, trust, cost, social influence, attitude, privacy, technology security, continuous improvement, perceptions of performance expectancy, compatibility, knowledge, and trust.